Legal protection of territorial waters from ship contaminants in Saudi law - Mohammed, Zubaida Abdul Hadi Atim (Journal of Economic, Administrative and Legal Sciences, 2018)
This article aims to identify the contaminants of ships in the territorial waters of the Kingdom of Saudi Arabia and review the international and regional conventions that have been concerned with the legal protection of regional waters from pollution. The subject was dealt with the presentation, analysis and interpretation of legal rules for the protection of the marine environment from ship pollutants, measures and liability for damage, and the article followed the comparative descriptive analytical approach. The results of the study indicate that the regional agreements and the Saudi environmental law are affected by the provisions of the international conventions for the protection of the marine environment, with special rules for emergency response to marine pollution.